2014
DOI: 10.1111/bph.12949
|View full text |Cite
|
Sign up to set email alerts
|

Preventing leptin resistance by blocking angiotensin II AT1 receptors in diet‐induced obese rats

Abstract: Background and Purpose AT1 receptor blockers (ARBs) represent an approach for treating metabolic syndrome due to their potency in reducing hypertension, body weight and onset of type 2 diabetes. The mechanism underlying ARB‐induced weight loss is still unclear. Experimental Approach Leptin resistance tests (LRTs) in diet‐induced obese or lean rats were conducted to determine whether telmisartan (8 mg·kg−1·day−1, 14 days) enhances leptin sensitivity. Phosphorylation of signal transducer and activator of transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 68 publications
6
34
1
Order By: Relevance
“…However, our data support a possible role for central ANG II signaling in SLR, as we have shown that ANG II AT 1A receptors specifically in leptin-sensitive cells are dispensable for BP control, but necessary for RMR control and thus energy balance. The general concept that AT 1 receptors mediate leptin sensitivity is also supported in a recent study by Müller-Fielitz et al (27). In contrast to the effects observed in our studies, it was demonstrated that peripheral treatment with the AT 1 antagonist telmisartan prevented leptin resistance in rats fed a high-calorie/ cafeteria diet (27).…”
Section: Discussionsupporting
confidence: 85%
“…However, our data support a possible role for central ANG II signaling in SLR, as we have shown that ANG II AT 1A receptors specifically in leptin-sensitive cells are dispensable for BP control, but necessary for RMR control and thus energy balance. The general concept that AT 1 receptors mediate leptin sensitivity is also supported in a recent study by Müller-Fielitz et al (27). In contrast to the effects observed in our studies, it was demonstrated that peripheral treatment with the AT 1 antagonist telmisartan prevented leptin resistance in rats fed a high-calorie/ cafeteria diet (27).…”
Section: Discussionsupporting
confidence: 85%
“…As previously described, CD consisted of commercial chocolate and cookies (62% carbohydrates, 25% fat, 6% protein, 2% fiber). Rats received only one kind of sweet per day (Müller-Fielitz et al, 2015;Schuchard et al, 2015). Furthermore, chocolate and cookie bars were changed daily in a regular manner (Müller-Fielitz et al, 2015;Schuchard et al, 2015).…”
Section: Feedingmentioning
confidence: 99%
“…Rats received only one kind of sweet per day (Müller-Fielitz et al, 2015;Schuchard et al, 2015). Furthermore, chocolate and cookie bars were changed daily in a regular manner (Müller-Fielitz et al, 2015;Schuchard et al, 2015). The third group were transgenic (TGR) rats, receiving standard chow food (TGR+chow, n = 6).…”
Section: Feedingmentioning
confidence: 99%
See 2 more Smart Citations